Laccase and peroxidase isoenzymes during leaf litter decomposition of Quercus ilex in a Mediterranean ecosystem (Soil Biology and Biochemistry, 2004)
The dynamics of leaf litter decomposition of Quercus ilex (L.) were investigated over a 2 year period by determining the activities and isoenzyme distribution of laccases and peroxidases. The analysis of isoenzymes was performed by isoelectric focusing on high stability pH gradients with high resolving power. The preparation of zymograms was carried out using the leaf litter extract without previous concentration. During litter decomposition, laccase and peroxidase activities changed as well as the type and number of enzyme isoforms. The activities of both enzymes were low (%0.017 and %0.031 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively) in ﬁrst year and increased in October–January of the second year of litter decay. The highest activities measured after 15–18 months of litter exposure (0.37G0.03 and 0.19G0.02 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively), showed that litter chemical composition affected the growth of ligninolytic microbial community. The activation energy for laccase and peroxidase reactions also changed during decomposition: the highest values (55G6 kJ molK1 for laccase and 60G6 kJ molK1 for peroxidase) occurred in autumn–winter, even if spatial changes were evidenced. Some enzyme isoforms (pIZ5.3 and 5.5 for laccase and pIZ5.0 and 5.1 for peroxidase, respectively), contributed more than others to the overall laccase and peroxidase activity, suggesting that some ligninolytic species bloomed in particular seasons of the year, even if other species with similar functional activities colonized the litter.